2019
DOI: 10.1001/jamanetworkopen.2019.6835
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Methods With National Cardiovascular Data Registry Models for Prediction of Risk of Bleeding After Percutaneous Coronary Intervention

Abstract: Key Points Question Can machine learning techniques, bolstered by better selection of variables, improve prediction of major bleeding after percutaneous coronary intervention (PCI)? Findings In this comparative effectiveness study that modeled more than 3 million PCI procedures, machine learning techniques improved the prediction of post-PCI major bleeding to a C statistic of 0.82 compared with a C statistic of 0.78 from the existing model. Machine learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 20 publications
0
51
0
1
Order By: Relevance
“…In the specific clinical context of predicting mortality from gastrointestinal bleeding, a systematic review demonstrated higher c ‐indices and predictive capacity with ML compared with clinical risk scores 38 . Another specific study aiming to predict bleeding risk following percutaneous coronary intervention reported that ML better characterized bleeding risk than a standard registry model 39 . An important distinction of our review was that we included disease‐specific studies that were published in the computer science literature, which were underrepresented in the aforementioned earlier comparisons of ML and CSMs.…”
Section: Discussionmentioning
confidence: 99%
“…In the specific clinical context of predicting mortality from gastrointestinal bleeding, a systematic review demonstrated higher c ‐indices and predictive capacity with ML compared with clinical risk scores 38 . Another specific study aiming to predict bleeding risk following percutaneous coronary intervention reported that ML better characterized bleeding risk than a standard registry model 39 . An important distinction of our review was that we included disease‐specific studies that were published in the computer science literature, which were underrepresented in the aforementioned earlier comparisons of ML and CSMs.…”
Section: Discussionmentioning
confidence: 99%
“…We first applied the XGBoost method using the gradient boosting decision tree algorithm to construct a risk prediction model. The model generates the importance score of each feature automatically by calculating the average improvement for each feature of the model after it was introduced to a branch [21][22][23][24]. A higher importance score indicated that the variable had a higher predictive value for the model.…”
Section: Prediction Model Using the Extreme Gradient Boosting Methodsmentioning
confidence: 99%
“…When using the data, it was randomly divided into two parts, with 80% used for developing window behavior models and 20% for model validation. This division has been popularly adopted in existing studies [45,46,49,51,61]. Table 3 has listed the calculated Pearson Correlation Coefficient for each potential influential factor considered in this study.…”
Section: Resultsmentioning
confidence: 99%
“…As a new machine learning method, the XGBoost (eXtreme Gradient Boost) method was firstly introduced by Chen [37] in 2016, and has been used in many other applications, such as automotive manufacturing [38], predicting building cooling load [39] and fault detection for HVAC systems [40]. In existing studies, much evidence was available about its advantages (stability, accuracy and efficiency) in modeling complex process over other conventional machine learning methods, such as SVM algorithm [41,42], logistic regression method [43][44][45][46][47][48][49] and KNN/decision tree [50,51]. This study, therefore, was designed to justify its contribution to modeling accuracy of occupant window behavior in buildings, mainly against the most conventional modeling approach, i.e.…”
Section: Introductionmentioning
confidence: 99%